شعر الغزل الصوفي في الأدب الماليزي الحديث - Aishah Isahak; Rosni Samah (Usuli Faqih Research Centre PLT, 2024)
The article discussed aboutMystical Ghazal Poems by studying the selected poetic texts of the most prominent contemporary poets such as Jamaluddin Darus, Nahmar Jamil, Suhaimi Haji Mohammed, Abdul Aziz Deraman, Hassan Basri Budiman, Ahmad Kamal Abdullah or Kemala, Abham T.R. The poets were chosen because their poetic texts which met the characteristics of the Ghazal, including its themes, and the predominance of vocabularyleading to the meanings of love and longing. After the article relied on the analytical descriptive study, it reached several results. The most important of these were the selected poetic texts are presenting several topics. These topics indicate that theideas of Mystical Ghazal Poems and its contents have remained until our present time, although the selected texts do not constitute a Ghazal as an independent art.